Epicardial adipose tissue and coronary artery calcification in psoriasis patients. (21st April 2014) - Torres, T.; Bettencourt, N.; Mendonça, D.; Vasconcelos, C.; Gama, V.; Silva, B.M.; Selores, M.
Abstract Background Psoriasis is a chronic, immune‐mediated disease associated with several cardio‐metabolic comorbidities, accelerated atherosclerosis and cardiovascular disease (CVD). Other causes beyond systemic inflammation and traditional cardiovascular risk factors (CVRF) may be implicated in the increased risk of CVD observed in these patients. Epicardial adipose tissue (EAT), a type of visceral adipose tissue surrounding the heart and coronary vessels has been implicated in the development of coronary artery disease, by endocrine mechanisms, but particularly by local inflammation. Objective To compare EAT volumes in psoriasis patients and controls using multidetector computed tomography (MDCT) and to analyse if eventual differences were independent from abdominal visceral adiposity; to determine, within psoriasis patients, its relation with subclinical atherosclerosis and other markers of cardiometabolic risk. Methods One hundred patients with severe psoriasis, without CVD underwent MDCT, with EAT and abdominal visceral fat (AVF) assessment and coronary artery calcification (CAC) quantification and were compared with 202 control patients. Results EAT volume was increased in psoriasis patients compared to control subjects, independently from age, sex and AVF, being, on average, 15.2 ± 4.41 mL higher (95% CI: 6.5–26.0, P = 0.001) than in controls. Moreover, psoriasis patients had a statistically significant higher risk of having subclinical atherosclerosis (OR 2.52, 95% CI: 1.23–5.16) than controls, after adjusting for traditional CVRF. Within psoriasis patients EAT volume was associated with subclinical atherosclerosis, independently of age, sex, psoriasis duration, classical CVRF and AVF. Conclusion This study showed that psoriasis was associated with increased EAT volume independently of visceral abdominal fat and with subclinical atherosclerosis. Within psoriasis patients EAT volume was independently associated with CAC. EAT may be another important contributor to the higher cardiovascular risk observed in psoriasis.